Correction: Testing and validating electroanalytical simulations. - Kätelhön, F; Compton, R (Royal Society of Chemistry, 2016)
Correction for 'Testing and validating electroanalytical simulations' by Enno Kätelhön and Richard G. Compton, Analyst, 2015, 140, 2592-2598.